PENGGUNAAN SIMBOL PADA PROSES INTERAKSI SIMBOLIK SISWA TUNAGRAHITA DAN GURU DI SEKOLAH LUAR BIASA - Rahman, Khafi Maulana; Purnomo, Agustina M.; Agustini, Agustini (Universitas Djuanda Bogor, 2020)
Symbolic interaction between students and teachers as a process of action and reaction involving an exchange of symbols. The symbols are formed and exchanged at the same time as the use of symbols in three levels, namely mind, self and society in symbolic interaction between mentally disabled students and teachers in special schools. The purpose of this study was to determine the use of mental retardation students and teachers in Special Schools. Descriptive qualitative research methods to explain phenomena accurately about existing facts. Data collection techniques through observation and in-depth interviews. Tunagrahita Teachers and Students in Special Schools become key informants in research, parents and closest friends become supporting informants. Data analysis technique is done by presenting data from Creswell. The theoretical foundation used in the research of Symbolic Interactionism from Mead. The results showed that the use of symbols in the mind, self and society level had an important role in the process of using symbols (manipulation and consumption) in the process of symbolic interaction. The conclusion of the research is the process of using symbols influenced by three levels of symbolic interaction, namely mind, self and society. Symbolic interaction at the level of society shows different levels according to the social and cultural background of students. Agreements that are built through symbolic interactions between teachers and students help students understand and understand social structures at school and at home, so they can constrain how they act and behave to suit other individuals.Â